2013
DOI: 10.1017/s1461145713000874
|View full text |Cite
|
Sign up to set email alerts
|

Effects of blockade of α4β2 and α7 nicotinic acetylcholine receptors on cue-induced reinstatement of nicotine-seeking behaviour in rats

Abstract: Exposure to environmental stimuli conditioned to nicotine consumption critically contributes to the high relapse rates of tobacco smoking. Our previous work demonstrated that non-selective blockade of nicotinic acetylcholine receptors (nAChRs) reversed the cue-induced reinstatement of nicotine seeking, indicating a role for cholinergic neurotransmission in the mediation of the conditioned incentive properties of nicotine cues. The present study further examined the relative roles of the two major nAChR subtype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 106 publications
2
20
0
Order By: Relevance
“…Responses on the inactive lever were recorded but had no programmed consequences. All rats received 25 daily sessions since our previous work has demonstrated successful establishment of stable nicotine self-administration under such a training schedule (Liu et al, 2008; Liu, 2014). Rats met the criterion of ≥ 10 infusions per session with ≤ 20% variation for at least three consecutive sessions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Responses on the inactive lever were recorded but had no programmed consequences. All rats received 25 daily sessions since our previous work has demonstrated successful establishment of stable nicotine self-administration under such a training schedule (Liu et al, 2008; Liu, 2014). Rats met the criterion of ≥ 10 infusions per session with ≤ 20% variation for at least three consecutive sessions.…”
Section: Methodsmentioning
confidence: 99%
“…The criterion for extinction was three consecutive sessions, in which the number of responses per session was ≤ 20% of the responses averaged across the last three sessions of the self-administration training phase. All of the rats underwent 10 extinction test sessions because our previous studies showed that nicotine-maintained responding was typically extinguished within 7–10 sessions (Liu et al, 2008; Liu, 2010; Liu, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Although the neuropharmacology that underlies relapse to smoking is not fully understood, animal models of relapse or reinstatement of nicotine seeking have been developed for investigating potential pharmacotherapies that may attenuate reinstatement following relapse triggers [79]. Interestingly, the first-line smoking cessation drug varenicline was shown not to block cue-induced relapse to nicotine seeking in rats [10], although it attenuated reinstatement when cues were combined with a nicotine priming injection [11] or a longer pretreatment time was used [12].…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that α4β2* nAChRs mediate nicotine primed, but not cue-induced, reinstatement of drug seeking. This is further supported by a study showing that cue-induced reinstatement of nicotine seeking is attenuated following pretreatment with an α7*, but not α4β2*, nAChR antagonist [99]. Interestingly, chronic nicotine exposure promotes formation of α7* nAChR-NMDA receptor heterodimeric protein complexes in the hippocampus, and blocking this interaction attenuates cue-induced nicotine seeking [100].…”
Section: Neurotransmitter Mechanisms Regulating Nicotine Seekingmentioning
confidence: 81%